2020
DOI: 10.3390/jcm9123834
|View full text |Cite
|
Sign up to set email alerts
|

Is Machine Learning a Better Way to Identify COVID-19 Patients Who Might Benefit from Hydroxychloroquine Treatment?—The IDENTIFY Trial

Abstract: Therapeutic agents for the novel coronavirus disease 2019 (COVID-19) have been proposed, but evidence supporting their use is limited. A machine learning algorithm was developed in order to identify a subpopulation of COVID-19 patients for whom hydroxychloroquine was associated with improved survival; this population might be relevant for study in a clinical trial. A pragmatic trial was conducted at six United States hospitals. We enrolled COVID-19 patients that were admitted between 10 March and 4 June 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 50 publications
11
14
0
Order By: Relevance
“…Specifically, we tested and observed both additive and interactive associations of HCQ and Covid-19 subtypes. Indeed, the high risk cluster was consistently associated with increased mortality across all models, while treatment with HCQ was generally associated with a halving of death risk, in line with previous evidence from both observational [613] and intervention studies [19]. While we already reported evidence suggesting a protective influence of HCQ against mortality in a largely overlapping sample [13], here we have further deepened this relationship by testing and reporting a significant association between cluster-by-HCQ interaction and mortality, which was driven by a differential association within the two clusters.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Specifically, we tested and observed both additive and interactive associations of HCQ and Covid-19 subtypes. Indeed, the high risk cluster was consistently associated with increased mortality across all models, while treatment with HCQ was generally associated with a halving of death risk, in line with previous evidence from both observational [613] and intervention studies [19]. While we already reported evidence suggesting a protective influence of HCQ against mortality in a largely overlapping sample [13], here we have further deepened this relationship by testing and reporting a significant association between cluster-by-HCQ interaction and mortality, which was driven by a differential association within the two clusters.…”
Section: Discussionsupporting
confidence: 87%
“…Notwithstanding it, to our knowledge only one study attempted so far a similar approach through the application of a supervised ML technique (gradient boosting), to identify those patients with likely beneficial effects of HCQ treatment. Interestingly, authors reported a reduction of in-hospital mortality within patients treated with HCQ, which was even more pronounced within those patients predicted to benefit most from the drug, in line with expectations [19].…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations